2009
DOI: 10.1111/j.1365-2613.2009.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Femur bone repair in ovariectomized rats under the local action of alendronate, hydroxyapatite and the association of alendronate and hydroxyapatite

Abstract: Summary An evaluation was made of the local action of alendronate sodium (A), hydroxyapatite (HA) and the association of both substances (A + HA), in different molar concentrations, on the femur bone repair of ovariectomized rats. Ninety-eight animals were divided into seven groups: control (C), starch (S), alendronate 1 mol (A1), alendronate 2 mols (A2), hydroxyapatite 1 mol (HA1), hydroxyapatite 2 mols (HA2) and the association of alendronate + hydroxyapatite (A + HA). Rats weighing about 250 g were ovariect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
(58 reference statements)
1
8
0
Order By: Relevance
“…Given that strontium has anti-osteoclastic potential, the present results corroborate previous results in which hydroxyapatite granules were mixed with an anti-resorptive drug, alendronate, and applied in similar defects in OVX rat femoral epiphyses [27]. In that study, Canettieri and co-authors found a closure of the bone defect after 21d using the HA alone, while, in the defects filled with alendronate-treated granules, no newly formed bone was found in the central area [27].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Given that strontium has anti-osteoclastic potential, the present results corroborate previous results in which hydroxyapatite granules were mixed with an anti-resorptive drug, alendronate, and applied in similar defects in OVX rat femoral epiphyses [27]. In that study, Canettieri and co-authors found a closure of the bone defect after 21d using the HA alone, while, in the defects filled with alendronate-treated granules, no newly formed bone was found in the central area [27].…”
Section: Discussionsupporting
confidence: 89%
“…In that study, Canettieri and co-authors found a closure of the bone defect after 21d using the HA alone, while, in the defects filled with alendronate-treated granules, no newly formed bone was found in the central area [27]. The authors suggested that the alendronate dose inside the defect may jeopardise the repair of the bone defect centrally, but, when molecules of the drug scattered and reached more distant sites, they may have favoured subperiosteal bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, titanium implants treated with an alendronate coating presented increased bone density and bone formation when residual peri‐implant postextraction socket defects around these implants were treated with GBR (Meraw & Reeve 1999). On the other hand, the systemic administration of alendronate failed to produce higher osseointegration surface or torque removal levels in healthy rabbits (Chacon et al 2006) and bone‐to‐implant contact in healthy dogs (Jakobsen et al 2009) Interestingly enough, local application of alendronate hindered femoral bone repair in ovariectomized rats (Canettieri et al 2009) while the soaking of allografts in alendronate resulted in compromised implant fixation because the alendronate treatment blocked formation of new bone and inhibited the resorption of the graft material around implants placed in the tibia of healthy dogs (Jakobsen et al 2007). Differences in the selected type of animal and treatment model as well as the observation period may have accounted for the opposing results.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the administration of antiosteoporotic drugs showed a positive effectiveness on BA% as observed in 51 out of 80 comparisons, primarily involving rat models. 20,21,[35][36][37][38] Also, 40 out of 72 comparisons showed positive effects of antiosteoporotic drugs on the BV%. [39][40][41] In contrast, several studies in the present meta-analysis indicated negative zero effects of the administration of antiosteoporotic drugs to enhance new bone formation by bone grafts.…”
Section: Discussionmentioning
confidence: 89%